2012
DOI: 10.1002/bdra.23030
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of studies of quality of life in children and adults with selected congenital anomalies

Abstract: The reviewed studies considered health status and functioning as a major determinant of QOL. More studies assessing QOL in patients with major congenital anomalies are needed, and those involving children should use age-adjusted, validated instruments to measure both health-related QOL and self-reported subjective wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…1 We observed a lack of consistency in the reviewed studies in relation to QoL in children with congenital conditions, with some reporting comparable 36,38,39 or even better 40 subjective QoL than control children, whereas others reported lower total or domain-specific scores. This inconsistency cannot be fully attributed to the type of condition, QoL measure used, or age differences, as some studies explored children of the same age groups with the same condition using the same instrument but reported discrepant findings.…”
Section: Determinants Of Findings and Comparison With Published Studiesmentioning
confidence: 80%
See 4 more Smart Citations
“…1 We observed a lack of consistency in the reviewed studies in relation to QoL in children with congenital conditions, with some reporting comparable 36,38,39 or even better 40 subjective QoL than control children, whereas others reported lower total or domain-specific scores. This inconsistency cannot be fully attributed to the type of condition, QoL measure used, or age differences, as some studies explored children of the same age groups with the same condition using the same instrument but reported discrepant findings.…”
Section: Determinants Of Findings and Comparison With Published Studiesmentioning
confidence: 80%
“…Studies were identified through comprehensive literature searches of OVID Medline, Embase, Web of Science, PsychINFO, and the Cochrane Database of Systematic Reviews. Databases were searched from January 1,1989, to June 30, 2013; the Convention on the Rights of the Child was published in 1989, 22 and it was believed that recognition for respecting the views of the child would have generated increased research for this age group. Relevant gray literature was identified by searching the NHS Evidence Database (http://evidence.nhs.uk/) and Turning Research Into Practice database (http://www.tripdatabase.com/).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 3 more Smart Citations